PEMBERDAYAAN UMKM DALAM UPAYA MENINGKATKAN NILAI EKONOMI DAN HUBUNGAN ANTAR LEMBAGA DI DESA OLEAN - Purborini, Ajeng Gendis; Alleyda, Nadia Azro; Saputra, Rifki; Amilia, Winda; Choiron, Miftahul; Rusdianto, Andrew Setiawan; Firstandika, Leader (Jurnal Hasil Pengabdian kepada Masyarakat Universitas Jember, 2025)
The economy has become a vital aspect of the Nation’s sustainability, the same goes for villages. The Economic value of a village becomes a key success indicator of synergy between the village's citizens and institutions. Olean Village is known for its tourist spot “Karang Kenek 26'' or KK26, which has become one of the important cores for the economy and SME empowerment. However, due to natural disasters, a tornado in 2022, and the COVID-19 pandemic, various sectors in Olean cease to operate. Aligning with the “Temu Inklusi Nasional 2023” event and the revitalization of KK26, KKN students become an important agent of change in SME empowerment in Olean Village. For effective empowerment, KKN students conduct an analysis and observation to simplify the synergy process between institutions and the citizens, thus developing a program consisting of socialization, service, training, and organization reinforcement.